Psycholinguistic and psychological features of ekphrasis - Svetlana V. Krutskaya; Lilia R. Nurtdinova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper deals with the psycholinguistic and psychological features of reader’s artistic images in O. Wilde’s novel “The Portrait of Dorian Grey”. The process of reading and images perception is analyzed in the perspective of co-creation. This process is analyzed on the example of the use of stylistic device ekphrasis. The definition of ekphrasis formulated by the authors and the brief historical path of its development in literature are given in the paper. On the basis of the use of this stylistic device the authors of this paper oppose the ethic and the esthetic plans of perception of poetic images in the novel O. Wilde "The Picture of Dorian Gray". It is shown how the usage of ekphrasis manages to form a moral position of the reader.